THE EFFECT OF TASK PLANNING DURATION ON THE STUDENTS ABILITY OF SPEAKING IN ENGLISH AS A FOREIGN LANGUAGE LEARNING PROCESS - Ketut Santi Indriani (STKIP Siliwangi, 2020)
This study was to find out the extent to task planning duration is applicable and influenced students’ oral presentation in terms of fluency, complexity and accuracy in English as a second language learning process. This study is a qualitative research method. The data were gathered through observation and documentation. The data was analyzed qualitatively by investigating the level of fluency, complexity and accuracy on students’ speech after being given a specific duration of task planning. Then, analyzed data was presented formally and informally.The subjects in this study were 25 learners of an English course institution in Denpasar, at the level of basic-4. Based on the analysis, it was found that task planning duration affects the fluency and accuracy of oral presentation. The longer the duration of the task planning, the higher level of fluency and accuracy of the language will be used by learners. This is caused by the time owned by the learners to plan ideas that would be presented related to the given topic and to formulate these ideas into correct sentences. However, the length of task planning does not affect the complexity of the language used by learners because of the complexity of the language depends on language competence possessed by learners. Although the duration of task planning was increased, the level of complexity of the language used did not change. Keywords: task planning, oral presentation, language learning